2017
DOI: 10.11591/ijeecs.v7.i3.pp773-785
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Modified HMAX Model Based on Combined with the Visual Featured Model

Abstract: <p>Identify objects based on modeling the human visual system, as an effective method in intelligent identification, has attracted the attention of many researchers. Although the machines have high computational speed but are very weak as compared to humans in terms of diagnosis. Experience has shown that in many areas of image processing, algorithms that have biological backing had more simplicity and better performance. The human visual system, first select the main parts of the image which is provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In [34,35] saliency map are affected by the properties of the object. Pourasad [24] proposed a Modified HMAX model based on combined with the visual featured model for HMAX (henceforth referred to as MHMAX) by calculating optimum patches based on their information. Ghodrati et al [25] found the better patches for HMAX by using genetic algorithm (henceforth referred to as GMAX).…”
Section: Introductionmentioning
confidence: 99%
“…In [34,35] saliency map are affected by the properties of the object. Pourasad [24] proposed a Modified HMAX model based on combined with the visual featured model for HMAX (henceforth referred to as MHMAX) by calculating optimum patches based on their information. Ghodrati et al [25] found the better patches for HMAX by using genetic algorithm (henceforth referred to as GMAX).…”
Section: Introductionmentioning
confidence: 99%